Complementary roles of two resilient neotropical mammalian seed dispersers - Almeida, Adriana de [UNESP] (2018)
Capuchin monkeys (Cebus spp. and Sapajus spp.) and coatis (Nasua spp.) coexist in most neotropical forests, including small forest remnants. Both capuchins and coatis eat fruit and disperse seeds, but little is known about whether their roles in seed dispersal are redundant or complementary. We compiled 49 studies from the literature on feeding by capuchins and/or coatis, of which 19 were comprehensive enough for our analyses. We determined the relative importance of fruit eating to each species and compared their diets. Additionally, we analysed the structure of three fruit-frugivore networks built with both animal groups and the fruits they eat and evaluated whether fruit traits influenced the network topology. Fruits represented the largest part of capuchin and coati diets, even though coatis have been known for their opportunistic and generalist diets. Capuchins and coatis also exhibited similar general diet parameters (niche breadth and trophic diversity). The three networks exhibited high connectance values and variable niche overlap. A Multiple Correspondence Analysis, failed to detect any trait or trait combination related to food use. In conclusion, capuchins and coatis both have generalist diets; they feed on many different species of fruits and exhibit important complementarity as seed dispersers. Both are likely to be particularly important seed dispersers in disturbed and fragmented forests.